Correction: Pharmaceutical crystalline complexes of sulfamethazine with saccharin: same interaction site but different ionization states. Issue 62 (14th June 2016) - Fu, Xue; Li, Jianhui; Wang, Lianyan; Wu, Bing; Xu, Xu; Deng, Zongwu; Zhang, Hailu
Abstract : Correction for 'Pharmaceutical crystalline complexes of sulfamethazine with saccharin: same interaction site but different ionization states' by Xue Fu et al., RSC Adv., 2016, 6, 26474–26478.